2018
DOI: 10.4067/s0718-95162018005002302
|View full text |Cite
|
Sign up to set email alerts
|

Serratia strains isolated from the rhizosphere of raulí ( Nothofagus alpina ) in volcanic soils harbour PGPR mechanisms and promote raulí plantlet growth

Abstract: Raulí is one of the most emblematic tree species of the Chilean temperate forests. Due to the high quality wood, this tree has been used for furniture and handicrafts manufacturing, which has positioned raulí as one of the most important commercial timber species in Chile. Currently, the international market demands sustainable production system for forest production, more specifically in plantlets production. In this regard, plant growthpromoting rhizobacteria (PGPR) inoculants may enhance the growth and surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The different letters indicate significant differences using Fisher's LSD test at P < 0.05 a Expressed as citric acid equivalent be different than the effect produced by each bacterium alone. However, other authors reported positive effects by using different consortiums in maize (Couillerot et al 2013), cucumber (Wang et al 2012), forage plants Mavuno grass (Sá et al 2019), and forest species Nothofagus alpina (Martínez et al 2018). These contradictory results with the use of combinations may be related to the correct concentration of each inoculum.…”
Section: Discussionmentioning
confidence: 96%
“…The different letters indicate significant differences using Fisher's LSD test at P < 0.05 a Expressed as citric acid equivalent be different than the effect produced by each bacterium alone. However, other authors reported positive effects by using different consortiums in maize (Couillerot et al 2013), cucumber (Wang et al 2012), forage plants Mavuno grass (Sá et al 2019), and forest species Nothofagus alpina (Martínez et al 2018). These contradictory results with the use of combinations may be related to the correct concentration of each inoculum.…”
Section: Discussionmentioning
confidence: 96%
“…Plant growth-promoting rhizobacteria as biofertilizer can improve plant growth by increasing the soil nutrient bioavailability and uptake by plant from a low-available soil nutrient pool (Gouda et al 2018). A wide range of PGPR can increase plant growth and yield, by such processes as nitrogen fixation; increasing the availability of Fe through production of siderophores; the production of phytohormones such as auxins, cytokinins, and gibberellin; declination of ethylene tension (Zaidi et al 2006;Martínez et al 2018); and production of organic acids, chelating agents, and mineral acids (like H 2 SO 4 and HNO 3 ) that can dissolve insoluble P to increase the availability of P and Zn in the soil (Dinesh et al 2018). Plant growth-promoting rhizobacteria can also promote plant growth by various mechanisms such as increasing the supply of nutrients, increasing root biomass or root surface area, and increasing nutrient uptake capacity of plants (Paungfoo-Lonhienne et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…and, EN9 was identified as Pantoea sp. Bacterial isolates which were identified as Bacillus, Serratia, and Pantoea were among common and widely reported genera belong to plant growth-promoting rhizobacteria group (Martínez et al, 2018;Aziz, 2015;Susilowati et al, 2015). E. coli strain EX2 which much related to clinical strain or human pathogen was rarely found as plant growth-promoting rhizobacterium species especially when exhibits multiple beneficial traits.…”
Section: Resultsmentioning
confidence: 99%